Small Watershed Rehabilitation and Management in a Changing Economic and Policy Environment - Fock, Achim; Cao, Wendao (World Bank, Washington, DC, 2016)
China is considered one of the most seriously eroded countries in the world. The many causes of this degradation can be divided into natural, human-induced and root causes. The consequences of watershed degradation are severe and reach even beyond the country’s boundaries. Addressing this issue requires a sustainable participatory and integrated watershed management approach. The Loess Plateau Watershed Rehabilitation Projects, implemented by the Ministry of Water Resources and co-financed by the World Bank has provided a model that is widely recognized for its great success. This calls for a paradigm shifting from a sectoral, top-down, technical and physical watershed intervention to a holistic, participatory, multisectoral and inter-agency collaborative, and result based watershed development.